2015
DOI: 10.3892/ol.2015.3398
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the PIK3CA gene as a prognostic factor in patients with colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) is one of the most common cancers worldwide, with ~700,000 mortalities occurring due to CRC in 2012. The treatment options are effective in a small percentage of patients, and it is important to identify specific biomarkers in order to determine patients for whom the available therapies will be beneficial. It has been hypothesised that the PIK3CA gene mutation may affect the response to therapy of patients with metastatic CRC. In the present study, primary tumour specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…16 This PIK3CA mutation rate is comparable to the mutation rates observed in Italy, France, Japan, and Australia (14%-17.8%), lower than the mutation rates in south Italy (28%) and higher than the mutation rates observed in Singapore, France, China, Poland, Switzerland, and past Indian study (2.2%-10.1%). 14,17,39,41,[45][46][47] PIK3CA mutations were higher in male patients (22.1%) than female patients (6.8%). Previous studies have either reported more PIK3CA mutations in females 41 or a even distribution between males and females.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…16 This PIK3CA mutation rate is comparable to the mutation rates observed in Italy, France, Japan, and Australia (14%-17.8%), lower than the mutation rates in south Italy (28%) and higher than the mutation rates observed in Singapore, France, China, Poland, Switzerland, and past Indian study (2.2%-10.1%). 14,17,39,41,[45][46][47] PIK3CA mutations were higher in male patients (22.1%) than female patients (6.8%). Previous studies have either reported more PIK3CA mutations in females 41 or a even distribution between males and females.…”
Section: Discussionmentioning
confidence: 96%
“…16 The PIK3CA mutation frequency at exon 9 (6.25%) and exon 20 (4.5%) is comparable to the Poland study (4.5% and 5.1%, respectively). 47…”
Section: Discussionmentioning
confidence: 99%
“…Though certain mutagenic processes have been reported as clock‐like , the consistency of these signals throughout tumour evolution remains unknown; (ii) certain mutations have profound effects on cell phenotype, meaning that mutations do not cause step‐wise changes in phenotype. For example, the loss of APC induces colon adenomatous growth – a radical phenotypic change – while other mutations have roles in progression ; and (iii) punctuated mutational mechanisms (such as those associated with CIN) are extremely common in cancer, but have an as yet undefined role in transformation, and additionally have complex phenotypic effects . The relationship of mutation rates and phenotypic change, and in turn the evolutionary tempo, is therefore multifaceted and cannot be simplified by using genetic data exclusively.…”
Section: Defining Cellular Species By Phenotypementioning
confidence: 99%
“…Most variants with confirmed oncogenic potential occurred in the helical domain encoded by exon 9 (E542K, E545A, E545G and E545K). Importantly, these variants have been recurrently reported in colon cancer [ 29 , 30 ] (see mutation mapper plots in Supplementary Figures 10-11 . Five different variants (G12V, G12D, G12S, G13D, A146V) were identified in KRAS (10/37 patients), all of which were present in the COSMIC database.…”
Section: Resultsmentioning
confidence: 99%